Cash for Care as Special Money: The Meaning and Uses of the Care Allowance in Close Relationships in the Czech Republic. Issue 2 (3rd April 2022) - Dudová, Radka
ABSTRACT: Investigating what happens when money in the form of a cash-for-care benefit enters family relationships, this article examines long-term family care in the Czech Republic where a "care allowance" was introduced in 2007. It compares two qualitative studies: one of adult children providing care to their parents and the other of mothers caring for a disabled child; in both cases, the adults are entitled to the benefit. The studies used narrative and in-depth interviews with forty-eight informal caregivers. Daughters providing care mostly earmarked the allowance as their parent's money or did not claim it at all, while sons viewed it as a contribution to pay for care services. Mothers interpreted it as compensation for their caring work. The different practices of earmarking special monies affirmed and maintained gendered normative expectations, thus explaining why the introduction of the benefit did not lead to the outcomes expected by policymakers. HIGHLIGHTS The introduction of a care allowance in the Czech Republic did not have the expected outcomes. The use of allowance money varied in cases of caring for a parent or child with disability. Gendered norms of care determined how the money was used. The most significant of these norms was that care should be provided personally and by women. The discretionary use of allowance money did not serve to improve caregivers' economic situations.